MECHANISMS FOR FORMING CAREER CHOICE MOTIVATION AMONG GRADUATING CLASS STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the pedagogical, psychological, and social factors influencing the formation of career choice motivation among graduating class students. It presents ideas and considerations about the necessary pedagogical mechanisms, methods, and tools for strengthening professional motivation.